Facile Synthesis of Manganese‐Cobalt‐Sulfur/Reduced Rraphene Oxide Composite as High Performing Faradaic Electrode. Issue 29 (2nd August 2021) - Chen, Lijun; Yin, Hongfeng; Li, Min; Chai, Lina; Wang, Biyao
Abstract: Herein, a composite, composed of MnCo‐sulfide heterojunction on the surface of rGO, is prepared via a facile one‐step hydrothermal vulcanization reaction. The physicochemical properties of the material are characterized using X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and X‐ray photoelectron spectroscopy. The as‐prepared composite is able to deliver a high specific capacitance of 2274.6 C g −1 at a scan rate of 1 mV s −1, and it is also able to exhibit good rate capability (retaining 1738.8 C g −1 at 10 mv s −1 ). A cell (MCS/rGO//activated carbon) is assembled, and it is able to achieve an energy density of 76.7 Wh kg −1 at a power density of 800 W kg −1 . Furthermore, a remarkable cyclic performance is recorded for cell, as it is able to achieve almost 100 % capacitance retention after cycling for 6000 cycles. Abstract : The MCS/rGO composite was prepared via a facile one‐step hydrothermal vulcanization reaction. The MCS/rGO electrodes show high specific capacity and excellent cycling stability. The as‐assembled MCS/rGO//activated carbon asymmetric cell device delivered an energy density of 76.7 Wh kg −1 at a power density of 800 W kg −1 . The asymmetric cell device demonstrated remarkable cyclic stability as it was able to achieve approximately 100 % capacitance retention after cycling for 6000 cycles.